Rediscovery of The Living Law in Natural Disaster Mitigation in Majene Regency, West Sulawesi Province, Indonesia - Bakri, Rahmat; Sulbadana, Sulbadana; Saharuddin3, Saharuddin; Ahmad, Asria Wayuni (Indonesia Law Review, 2022)
The living law and state law are two schools of law that are always dialectical in the development of law in a country. If the two can be synergized properly, then the legal function will run effectively and the legal objectives will be achieved. In the context of natural disaster mitigation in Indonesia, the synergy between the living law and state law can be proposed as a solution to streamline the various existing laws. This study aims to reidentify natural disaster mitigation models a previous result of the collective creativity of the people of Totolisi Sendana Village, Majene Regency, West Sulawesi Province in responding to the 1969 earthquake and tsunami. As a living law, mitigation models that have been institutionalized can remain relevant in the face of similar events in the future as long as they are adapted to the dynamics of community development and integrated with various positive laws established by the state.